PENGARUH ROA, ROE, DAN EPS TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN YANG TERDAFTAR PADA BEI PERIODE 2018-2022 - Nugroho, Johannes; Pangaribuan, Leonard; Prastio, Wiwin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
Return On Asset (ROA), Return On Equity (ROE), and Earning Per Share (EPS) are profitability ratios used to determine the company's ability to generate profits in the current year and its prospects in the future. The purpose of this study was to determine the effect of Return on Asset (ROA), Return on Equity (ROE), and Earning Per Share (EPS) on the stock price of banking companies listed on the Indonesia Stock Exchange. The object of this research is banking companies listed on the Indonesia Stock Exchange for the period 2018-2022. Sampling was carried out using non-probability sampling technique with purposive sampling method. The total sample used was 33 companies and the observation unit was 165 data. The data analysis technique used is the regression coefficient similarity test, descriptive statistical analysis, classical assumption test, determination coefficient test, F test, and t test using the IBM SPSS Statistics 29 program. The results of this research show that return on assets and return on equity do not have a significant effect on the share prices of banking companies listed on the BEI for the 2018-2022 period, while earnings per share have a significant positive effect on the share prices of banking companies listed on the BEI for the 2018-2022 period.